The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsami.8b18055
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Alignment of Polymer Semiconductor Nanowires for Efficient Charge Transport via Controlled Evaporation of Confined Fluids

Abstract: Long-range alignment of conjugated polymers is as critical as polymer chain packing for achieving efficient charge transport in polymer thin films used in electronic and optoelectronic devices. Here, the present study reports a facile, scalable strategy that enables the deposition of macroscopically aligned polymer semiconductor nanowire (NW)-array films with highly enhanced charge carrier mobility, using a modified controlled evaporative self-assembly (MCESA) technique. Organic field-effect transistors (OFETs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…For semiconductor 2 (Figure h) and 1 (Figure i) films AFM reveals the presence of large plate like grains consisting of flat terraces closely packed, morphological features which favor charge transport. It can be concluded that both the utilization of the shearing process and the achievement of stronger molecular interactions is likely responsible for the enhanced OFET performance. ,, On the other hand, among the DRDTT films only that of 1R exhibit crystal features, in agreement with the GIXRD analysis and the decent carrier mobility of this semiconductor.…”
Section: Results and Discussionsupporting
confidence: 73%
“…For semiconductor 2 (Figure h) and 1 (Figure i) films AFM reveals the presence of large plate like grains consisting of flat terraces closely packed, morphological features which favor charge transport. It can be concluded that both the utilization of the shearing process and the achievement of stronger molecular interactions is likely responsible for the enhanced OFET performance. ,, On the other hand, among the DRDTT films only that of 1R exhibit crystal features, in agreement with the GIXRD analysis and the decent carrier mobility of this semiconductor.…”
Section: Results and Discussionsupporting
confidence: 73%
“…This reduction is possibly a result of the excess amount of methanol favoring solute nucleation over crystal growth. As a result, the number of interfaces between crystalline regions would increase, resulting in an increase in the number of grain boundaries (i.e., the number of interfaces between crystallites) that hinder efficient charge transfer (Figure 4e,f) [7,35,36]. Figure 5b displays charge transfer curves for OFETs prepared from P3HT solutions pre-treated with methanol vapor for 0 and 3 h, and the curves obtained are characteristic of p-channel OFETs in accumulation mode.…”
Section: Resultsmentioning
confidence: 99%
“…Semiconducting conjugated polymers (CPs) have drawn considerable attention as promising building blocks for use in opto-electronic applications including light-emitting diodes (LEDs) [1], organic photovoltaic cells (OPVs) [2,3], and organic field-effect transistors (OFETs) [4,5]. Their key advantages such as low weight, flexibility, and solution processability may support the production of low-cost, large-area devices [6,7]. The π–π stacking of CPs through p-orbital interactions renders intriguing anisotropic opto-electronic properties [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This might be presumably due to some unintentional doping effects and charge trapping at the compound/oxide and/or the grain boundary interfaces according to the literature reported. 25 The DPP-3FBVCNT-based devices showed almost similar threshold voltages to those of DPP-2FBVCNT-based devices, maybe because of their nearly similar HOMO/LUMO energy levels, which might be due to the similar conformational lock effects from the F…H bonds in the two compounds according to previous research performed by our group. 26,27 From the above results, it can be seen that in these DPP-DBVCNT-based organic conjugated small molecules, the substitution and the position of the F atoms introduced into the benzene rings of the donor units had significant effects on the charge carrier transport.…”
Section: Charge Carrier Transport Performancementioning
confidence: 53%